Faktor-Faktor yang Berhubungan dengan Kinerja Pemadam Kebakaran di Dinas Pemadam Kebakaran - Rosela, Florentina Dian; Koesyanto, Herry (Indonesian Journal of Public Health and Nutrition, 2021)
Background: The Semarang City Fire Department has a vision that reads "Creating a sense of security for the people of Semarang City from the danger of fire", but in reality the number of fire disasters in Semarang City continues to increase every year. Referring to the vision that has been set, this means that the performance of the Fire Department has decreased because it has not been able to implement the vision properly. The purpose of this study was to determine the factors related to the performance of firefighters in the Semarang City Fire Department. Methods: This type of research is quantitative research with cross sectional method. The population in this study were 330 firefighters. The research sample amounted to 77 respondents, the sampling technique was total random sampling using chi-square data analysis. The instruments used are questionnaires and checklist sheets. Results: chi-square test as follows: (1) perception of facilities and infrastructure (p = 0.000), (2) training (p = 0.000), (3) counseling (p = 0.000). Conclusion: The conclusion of this study is that there is a relationship between perceptions of facilities and infrastructure, training, and counseling on performance at the Semarang City Fire Department.